The Pragmatic Functions of Repetition in TV Discourse - Rabab'ah, Ghaleb; AbuSeileek, Ali Farhan (Research in Language, 2012)
Since repetition is a natural phenomenon used to perform various functions in interactional discourse, adopting a pragmatic analysis to the discourse of Dr. Phil and his guests on Dr. Phil's TV show, this study attempted to explore the pragmatic functions of such repetitions as used by English native speakers. The data were gathered from conversations between native speakers of English, and based on 7 full episodes of Dr. Phil's TV Show. The researchers watched, and studied these episodes on YouTube. The study revealed that one of the salient features of TV discourse is repetition, which is employed to perform a variety of language functions. Repetition was used to express emphasis, clarity, emotions, highlight the obvious, be questionable, express annoyance, persuasion, express surprise, give instructions, and as a filler in order to take time, when the speaker was searching for a proper word to say what would come next. The study concluded that these findings had significant implications for EFL/ESL teachers and the interlanguage development of EFL/ESL learners.